Perforin expression in Theileria parva specific Cytotoxic T Cells correlates with Cytotoxicity - Wendoh, J.; Waihenya, R.; Saya, R.; Awino, Elias; Nene, Vishvanath M.; Steinaa, Lucilla (Scientific Research Publishing, Inc., 2014)
Theileria parva is a protozoan parasite that causes the disease East Coast fever in cattle which results in major economic losses in Eastern, Central and Southern Africa. Efforts to generate vaccines involve measurements of cytotoxic activity since CD8 cells are believed to be responsible for protection of the animals. CTL assays are time consuming, and may require use of radioactive material and they also impose a considerable amount of in vitro work, which may skew the response compared to ex vivo assays. Hence it would be beneficial to identify other markers that correlate with the cytotoxicity. In this in vitro study we examined if the number of tetramer positive CD8 cells and the staining intensity of these correlated with lysis of the target cells. Furthermore, we investigated if the expression of the activation marker perforin correlated with the cytotoxicity. Perforin is involved in permeabilization of the cell membrane of the target cell. Bulk CTL lines and purified CD8 cell lines generated from cattle of the A18 BoLA (MHC) type were analysed for the Theileria parva specific immune responses using a peptide-MHC tetramer and antibodies for perforinin FACS analysis. Thelysis of target cells was determined by a chromium release assay. Results demonstrate that the percentage of tetramer positive cells, in six cell lines generated against the whole parasite, correlate with killing of PBMC pulsed with the peptide. The product of the percentages of perforin and tetramer double positive cells and the net MFI of perforin showed a perfect correlation with the cytotoxicity of the peptide pulsed PBMC. Likewise, the product of percentage perforin positive cells and the staining intensity had the best significant correlation with killing of the pulsed PBMC. The present results suggest that perforin could be a possible biomarker for the cytotoxicity to Theileria parva infections/immunizations.